Possible mechanism for donor DNA binding and transport in Haemophilus. - Kahn, M E (1982)
Morphological differences were observed in competent and noncompetent Haemophilus parainfluenzae and Haemophilus influenzae when thin sections of these cells were examined by electron microscopy. The membranous extensions present on the surface of competent H. parainfluenzae cells disappeared on treatment with transforming DNA, while vacuole-like structures appeared in the periplasm. Noncompetent cells had 1/5th as many extensions on their surface as competent cells, and no vacuoles were observed after treatment with homologous DNA. Competent cells treated with radiolabeled DNA were disrupted and the clarified lysate was centrifuged on CsCl density gradients. Material having a density of 1.34 g/ml was found to contain the majority of the DNase-resistant radioactive DNA recovered from the bacteria and was shown by electron microscopy to be composed of membrane vesicles. The polypeptide composition of this dense membrane fraction was similar to that of H. parainfluenzae outer membrane.